Indonesia: Indonesia - Badrudin, Badrudin; Puspita Sari, Pipit; Hidayat, Wahyu (MUNTAZAM, 2023)
Student morals are currently very worrying, which is motivated by various negative cases such as bullying and sexual harassment that occur in schools today. Around 41% of students in Indonesia have experienced bullying or been treated rudely by their classmates. The impact of this situation clearly shows the need to reconsider character education to overcome this negative trend. Therefore, it is important to have a character education management program managed by the school, because students are not only focused on developing intelligence and knowledge, but it is also important to have good morals. This research aims to determine the management of character education, the development of students' morals in madrasas, and the relationship between character education management and the development of students' morals in private Msanawiyah Madrasas, Cibiru District, Bandung City . This research uses a quantitative approach with descriptive correlational analysis methods. Data collection techniques using questionnaires. After the data is collected, the data is processed using the SPSS program, to test research instruments (validity and reliability), statistical analysis (partial analysis per indicator and interpretation of variables), prerequisite tests (data normality and data linearity), and correlation tests (correlation coefficient and coefficient of determination) . The results of this research state that character education management with moral development of students in madrasas has a correlation with a significance value of 0.000 <0.05. Based on the results of the correlation analysis calculation, the correlation coefficient obtained was 0.598. It is at a moderate level of strength, because it is in the 0.400 – 0.599 category range. The type of relationship between the variable Character Education Management and Student Moral Development in Madrasas leads to a positive relationship by looking at the Pearson correlation number, namely 0.598 with no negative sign (-) in that number, so the relationship between the two variables is in the same direction and means that the higher the Character Education Management the higher the morals of students in Madrasah will be. Then, the coefficient of determination (R square) value was obtained at 0.358, meaning that the contribution of the Character Education Management variable to the variable Y, Student Moral Development at the State Madrasah Tsanawiyah, Cibiru District, Bandung City was 35.8%.